2012
DOI: 10.1007/s12031-012-9755-z
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PACAP/ADNP Signaling in the Resistance to Cell Death in Malignant Peripheral Nerve Sheath Tumor (MPNST) Cells

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are sarcomas able to grow under conditions of metabolic stress caused by insufficient nutrients or oxygen. Both pituitary adenylate cyclase-activating polypeptide (PACAP) and activity-dependent neuroprotective protein (ADNP) have glioprotective potential. However, whether PACAP/ADNP signaling is involved in the resistance to cell death in MPNST cells remains to be clarified. Here, we investigated the involvement of this signaling system in the survival response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 36 publications
5
33
0
Order By: Relevance
“…In this regard, previous works have proposed that the axon-cell contact independent ability of Schwann cells to switch from a non-myelinating to a myelinating state in vitro may partly depend on their differentiation state, which can be triggered by serum withdrawal [30,9]. In line with these evidences, we have previously found that the RT4 schwannoma cell line used in the present study behaved similarly to primary Schwann cells when starved from serum, acquiring a more differentiated-like phenotype [7]. Furthermore, when starved for short periods, RT4 schwannoma cells showed increased endogenous expression of PACAP and related receptors both at mRNA [7] and protein levels, as observed in the present study ( Fig.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In this regard, previous works have proposed that the axon-cell contact independent ability of Schwann cells to switch from a non-myelinating to a myelinating state in vitro may partly depend on their differentiation state, which can be triggered by serum withdrawal [30,9]. In line with these evidences, we have previously found that the RT4 schwannoma cell line used in the present study behaved similarly to primary Schwann cells when starved from serum, acquiring a more differentiated-like phenotype [7]. Furthermore, when starved for short periods, RT4 schwannoma cells showed increased endogenous expression of PACAP and related receptors both at mRNA [7] and protein levels, as observed in the present study ( Fig.…”
Section: Discussionsupporting
confidence: 86%
“…3C), while both PAC1 and VPAC2 expression levels were augmented by about 1.7-folds in SS cells (t 4 ¼4.656 and t 4 ¼ 2.795, p¼ 0.0096 and p¼ 0.049 vs. Ctrl, respectively). These results, together with previous evidences [7], suggest that a short period of serum withdrawal might be sufficient to trigger the activation of the endogenous PACAP/VIP signaling system, possibly through an autocrine/paracrine loop.…”
Section: Serum Starvation Increases the Endogenous Expression Of Pacasupporting
confidence: 77%
See 2 more Smart Citations
“…ADNP interacts with components of the BAF complex, the eukaryotic equivalent of the SWI/SNF complex in yeast, which is involved in the regulation of gene expression (34). In cancer cells, ADNP regulates cell growth and differentiation and, under stress conditions, exhibits expression changes leading to cancer progression (35). In contrast, in intestinal cancer cells, downregulation of ADNP by antisense oligodeoxynucleotides upregulates the TS p53 and reduces the viability of intestinal cancer cells (36).…”
Section: Discussionmentioning
confidence: 99%